Bioactive multiple-bent MWCNTs for sensitive and reliable electrochemical detection of picomolar-level C-reactive proteins. Issue 18 (4th March 2020) - Jang, Yeongseok; Kim, Hyojae; Yang, Seung Yun; Jung, Jinmu; Oh, Jonghyun
Abstract : Multiple-bent MWCNTs with highly sensitive electrochemical impedance were introduced for the ultrasensitive and reliable detection of CRP. Abstract : We present multiple-bent multi-walled carbon nanotubes (MWCNTs) that enable the picomolar detection of C-reactive protein (CRP), which is considered to be a promising biomarker for various diseases. The MWCNTs were grown via chemical vapor deposition repeating the asymmetric catalytic CNT growth on atypical carbon nanoparticles that were generated by carbon coating on a silicon substrate. The multiple-bent MWCNTs with the carbon film (CF) possessed abundant hydrophilic functional groups (–COOH and –OH) at their bending sites, resulting in enhanced bioadhesion to collagen and platelets, compared to MWCNTs grown without a CF layer. Interestingly, the bent MWCNTs enhanced the reliability and sensitivity of the electrochemical detection at low CRP concentrations, possibly due to molecular affinity at the bent site. The bioactive bent MWCNTs can play a significant role in ultrasensitive biosensors to improve their detection limit, thereby achieving early detection and monitoring of CRP-related diseases such as cardiovascular events and melanoma.